The Effectiveness of Manipulative Display Tool Assisted-Stay at Home Learning on the Students’ Problem Solving - Laely Rizki Maulida; Isti Hidayah; Sunyoto Eko Nugraha (Universitas Negeri Semarang, 2022)
The use of manipulative display tool is able to draw the interest of the students and, at the same time, motivate them to pay attention to the learning process. The manipulative display tool itself may serve as an aid to deliver or to explain the mathematical concepts correctly. In addition to the problem, and specific to the context of the study, the problem-solving capacity of the students in SD Negeri Banjarsari the District of Ajibarang the Regecy of Banyumas is still low. The study aims to identify the effectiveness of the manipulative display tool assisted-stay at home learning against problem-solving skills of the students. In conducting the study, the method that has been implemented is the mixed method. The study used the sequential explanatory design using the sequential combination of the quantitative and the qualitative research method. The number of the subjects in the study consist of 88 respondents. The quantitative samples for the study are gathered through the cluster random sampling technique while the qualitative samples for the study are gathered through the purposive sampling technique. Furthermore, the data gathering method that has been used in the study consists of test, questionnaire, interview, and documentation. After the data have been gathered, the data are analysed by using the independent sample t-test and the N-gain test. Based on the results of the study, it is found that there have been differences on the mathematical problem-solving learning results between the students in the experimental group and the control group with the significance value .000 < 0.05. in addition, it is also found that the pre-test and the post-test results of the experimental group have increased namely 0.59 and 0.38 as these results belong to the moderate category. Hence, these findings show that the improvement on the learning results has been influenced by the effective of the manipulative display tool-assisted stay at home learning and the open-ended questions.